Impact of pharmacy worker training and deployment on access to essential medicines for children under five in Malawi: a cluster quasi-experimental evaluation - Joseph B. Babigumira; Solomon J. Lubinga; Alisa M. Jenny; Erin Larsen-Cooper; Jessica Crawford; Charles Matemba; Andy Stergachis (BMC, 2017)
Abstract Background Poor access to essential medicines is common in many low- and middle-income countries, partly due to an insufficient and inadequately trained workforce to manage the medicines supply chain. We conducted a prospective impact evaluation of the training and deployment of pharmacy assistants (PAs) to rural health centers in Malawi. Methods A quasi-experimental design was used to compare access to medicines in two districts where newly trained PAs were deployed to health centers (intervention) and two districts with no trained PAs at health centers (comparison). A baseline household survey and two annual post-intervention household surveys were conducted. We studied children under five years with a history of fever, cough and difficulty in breathing, and diarrhea in the previous two weeks. We collected data on access to antimalarials, antibiotics and oral rehydration salts (ORS) during the childrens' symptomatic periods. We used difference-in-differences regression models to estimate the impact of PA training and deployment on access to medicines. Results We included 3974 children across the three rounds of annual surveys: 1840 (46%) in the districts with PAs deployed at health centers and 2096 (53%) in districts with no PAs deployed at health centers. Approximately 80% of children had a fever, nearly 30% had a cough, and 43% had diarrhea in the previous two weeks. In the first year of the program, the presence of a PA led to a significant 74% increase in the odds of access to any antimalarial, and a significant 49% increase in the odds of access to artemisinin combination therapies. This effect was restricted to the first year post-intervention. There was no effect of presence of a PA on access to antibiotics or ORS. Conclusion The training and deployment of pharmacy assistants to rural health centers in Malawi increased access to antimalarial medications over the first year, but the effect was attenuated over the second year. Pharmacy assistants training and deployment demonstrated no impact on access to antibiotics for pneumonia or oral rehydration salts for diarrhea.